Resiliensi Akademik Siswa Sekolah Menengah Pertama dalam Mengikuti Pembelajaran Tatap Muka Terbatas (TMT) di Daerah Khusus Ibukota (DKI) Jakarta - Afi Faturrohmah; Dony Darma Sagita (Kuras Institute, 2022)
This study aims to identify the level of academic resilience of junior high school students (First Secondary School) during the period of Pembelajaran Tatap Muka Terbatas (Limited Face-to-Face Learning) during the Covid-19 pandemic. The type of research using quantitative descriptive design with the population used is Muhammadiyah Junior High School 2 Jakarta (n=379). The sampling technique uses Convention sampling. This study used a questionnaire adapted from the Indonesian version of The Academic Resilience Scale-30 (ARS-30) with a lycert scale. The data obtained will be analyzed using categorization tests through the IBM SPSS Statistics 26 and Microsoft Excel applications. The results of the study showed that 311 students (82.1%) had a high academic resilience rate and 68 students (17.9%) had a moderate resilience rate determined through measuring academic resilience dimensions (1) Perseverance or persistence, (2) Reflecting and Adaptive Help Seeking, (c) Negatif Affect and Emotional Response. Therefore it can be inferred that the academic resilience rate of junior high school students in the Pembelajaran Tatap Muka Terbatas period has a relatively high category.